Vegetation history and Picea abies (L.) Karst. establishment in the Härjedalen province (central Sweden) - Rodríguez, Eva (2008)
The traditional theory about Picea abies (L.) Karst. arrival and establishment in Sweden is being revised. Until Picea abies megafossils were radiocarbon dated between the late-Glacial and the mid-Holocene (Kullman, 2000), it was widely accepted that Picea abies established at the Swedish East coast approximately 3500 B.P., then spreading to the South and West. Early- to mid-Holocene occurrence of Picea abies in previous pollen diagrams, such as Lundqvist (1969), that were considered as long distance pollen transport, could now be interpreted as early outposts of Picea abies. The overall aim of this project is to reconstruct the past vegetation in central Sweden. The specific question is whether pollen records can verify the early-Holocene Picea abies establishment in Sweden as is suggested by Lundqvist (1969). A pollen analysis study was performed in Stenhammaren, in the Härjedalen province (central Sweden), a few kilometres from the site with high early pollen proportion of Picea abies. The results permit the reconstruction of the past vegetation in the site, however no early Picea abies pollen has been found. Nevertheless, the presence of Picea abies trees near the study site in the early-Holocene should not be discarded, and further research is needed.